Conceptual Framework of Innovation Strategy in SMEs - Nizar Alam Hamdani; Sukma Nugraha; Pupung Purnamasari (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
The use of new innovations as tools to face competition is indeed considered effective enough to win the market. The absence of innovation will make consumers feel bored, leave the product, and we can be sure the business will sink amid the hustle and bustle of competition. This study analyzes the application of innovation strategy concepts in companies and SMEs. The approach in this study is scientific analysis of the literature and previous research on innovation strategies in SMEs. Based on the results of the study, the conceptual framework of the application of SME strategies was obtained, both dimensions, indicators and key to success and obstacles. The implication of this research is that there is an appropriate concept that can be used to develop research in the field of innovation strategy.